HFC-43-10mee atmospheric abundances and global emission estimates - Arnold, Tim; Ivy, Diane J; Harth, Christina M; Vollmer, Martin K; Mühle, Jens; Salameh, Peter K; Paul Steele, L; Krummel, Paul B; Wang, Ray H J; Young, Dickon; Lunder, Chris R; Hermansen, Ove; et al. (Geophysical Research Letters, 2014)
We report in situ atmospheric measurements of hydrofluorocarbon HFC-43-10mee (C5H2F10; 1,1,1,2,2,3,4,5,5,5-decafluoropentane) from seven observatories at various latitudes, together with measurements of archived air samples and recent Antarctic flask air samples. The global mean tropospheric abundance was 0.21 ± 0.05 ppt (parts per trillion, dry air mole fraction) in 2012, rising from 0.04 ± 0.03 ppt in 2000. We combine the measurements with a model and an inverse method to estimate rising global emissions—from 0.43 ± 0.34 Gg yr−1 in 2000 to 1.13 ± 0.31 Gg yr−1 in 2012 (~1.9 Tg CO2-eq yr−1 based on a 100 year global warming potential of 1660). HFC-43-10mee—a cleaning solvent used in the electronics industry—is currently a minor contributor to global radiative forcing relative to total HFCs; however, our calculated emissions highlight a significant difference from the available reported figures and projected estimates.
Keywords: Antarktis; atmosfæren; forurensning; massespektrometri; meteorologi; målinger; utslipp

Late Holocene climate change recorded in proxy records from a Bransfield Basin sediment core, Antarctic Peninsula - Barnard, Alex; Wellner, Julia S; Anderson, John B (Polar Research, 2014)
The glacimarine environment of the Antarctic Peninsula region is one of the fastest warming places on Earth today, but details of changes in the recent past remain unknown. Large distances and widespread variability separate late Holocene palaeoclimate reconstructions in this region. This study focuses on a marine sediment core collected from ca. 2000 m below sea level in the Central Bransfield Strait that serves as a key for understanding changes in this region. The core yielded a high sedimentation rate and therefore provides an exceptional high-resolution sedimentary record composed of hemipelagic sediment, with some turbidites. An age model has been created using radiocarbon dates that span the Late Holocene: 3560 cal yr BP to present. This chronostratigraphic framework was used to establish five units, which are grouped into two super-units: a lower super-unit (3560–1600 cal yr BP) and an upper super-unit (1600 cal yr BP–present), based on facies descriptions, laser particle size analysis, x-ray analysis, multi-sensor core logger data, weight percentages and isotopic values of total organic carbon and nitrogen. We interpret the signal contained within the upper super-unit as an increase in surface water irradiance and/or shortening of the sea-ice season and the five units are broadly synchronous with climatic intervals across the Antarctic Peninsula region. While the general trends of regional climatic periods are represented in the Bransfield Basin core we have examined, each additional record that is obtained adds variability to the known history of the Antarctic Peninsula, rather than clarifying specific trends. Keywords: Antarctic Peninsula; palaeoclimate; Holocene; marine; isotopes.
Keywords: Antarktis; geofysikk; geokjemi; paleoklimatologi; sedimentologi

A community-based geological reconstruction of Antarctic Ice Sheet deglaciation since the Last Glacial Maximum - Bentley, Michael J.; Ó Cofaigh, Colm; Anderson, John B.; Conway, Howard; Davies, Bethan; Graham, Alastair G.C.; Hillenbrand, Claus-Dieter; Hodgson, Dominic A.; Jamieson, Stewart S.R.; Larter, Robert D.; Mackintosh, Andrew; Smith, James A.; et al. (Reconstruction of Antarctic Ice Sheet Deglaciation (RAISED), 2014)
A robust understanding of Antarctic Ice Sheet deglacial history since the Last Glacial Maximum is important in order to constrain ice sheet and glacial-isostatic adjustment models, and to explore the forcing mechanisms responsible for ice sheet retreat. Such understanding can be derived from a broad range of geological and glaciological datasets and recent decades have seen an upsurge in such data gathering around the continent and Sub-Antarctic islands. Here, we report a new synthesis of those datasets, based on an accompanying series of reviews of the geological data, organised by sector. We present a series of timeslice maps for 20 ka, 15 ka, 10 ka and 5 ka, including grounding line position and ice sheet thickness changes, along with a clear assessment of levels of confidence. The reconstruction shows that the Antarctic Ice sheet did not everywhere reach the continental shelf edge at its maximum, that initial retreat was asynchronous, and that the spatial pattern of deglaciation was highly variable, particularly on the inner shelf. The deglacial reconstruction is consistent with a moderate overall excess ice volume and with a relatively small Antarctic contribution to meltwater pulse 1a. We discuss key areas of uncertainty both around the continent and by time interval, and we highlight potential priorities for future work. The synthesis is intended to be a resource for the modelling and glacial geological community.
Keywords: Antarktis; Modelling; deglasiasjon; geologi; glasiologi; innlandsis

Svartelisting i isødet - Christensen, Stig H (LO-Aktuelt, 2014)
Hvalfangst-eventyret i Antarktis fra 1905 kostet menneskeliv og blodslit. Hvalfangernes forsøk på å organisere seg ble møtt med svartelisting, utestengelse og arrestasjoner.
Keywords: Antarktis; Sørishavet; arbeidsforhold; fagforbund; hvalfangere; hvalfangst; pelagisk; sjøfolk

Contrasting strategies of resistance vs. tolerance to desiccation in two polar dipterans - Everatt, M J; Convey, P; Worland, M R; Bale, J S; Hayward, S A L (Polar Research, 2014)
Low water availability is one of the principal stressors for terrestrial invertebrates in the polar regions, determining the survival of individuals, the success of species and the composition of communities. The Arctic and Antarctic dipterans Heleomyza borealis and Eretmoptera murphyi spend the majority of their biennial life cycles as larvae, and so are exposed to the full range of environmental conditions, including low water availability, over the annual cycle. In the current study, the desiccation resistance and desiccation tolerance of larvae were investigated, as well as their capacity for cross-tolerance to temperature stress. Larvae of H. borealis showed high levels of desiccation resistance, only losing 6.9% of their body water after 12 days at 98.2% relative humidity (RH). In contrast, larvae of E. murphyi lost 46.7% of their body water after 12 days at the same RH. Survival of E. murphyi larvae remained high in spite of this loss (>80% survival). Following exposure to 98.2% RH, larvae of E. murphyi showed enhanced survival at −18°C for 2 h. The supercooling point of larvae of both species was also lowered following prior treatment at 98.2% RH. Cross-tolerance to high temperatures (37 or 38.5°C) was not noted following desiccation in E. murphyi, and survival even fell at 37°C following a 12-day pre-treatment. The current study demonstrates two different strategies of responding to low water availability in the polar regions and indicates the potential for cross-tolerance, a capacity which is likely to be beneficial in the ever-changing polar climate. Keywords: Acclimation; dipteran; supercooling point; temperature; cross-tolerance.
Keywords: Antarktis; diptera; polarområdene; temperatur; tovinger; uttørking; virvelløse dyr

Counteracting the climate effects of volcanic eruptions using short-lived greenhouse gases - Fuglestvedt, Jan S.; Samset, Bjørn H.; Shine, Keith P. (Geophysical Research Letters, 2014)
A large volcanic eruption might constitute a climate emergency, significantly altering global temperature and precipitation for several years. Major future eruptions will occur, but their size or timing cannot be predicted. We show, for the first time, that it may be possible to counteract these climate effects through deliberate emissions of short-lived greenhouse gases, dampening the abrupt impact of an eruption. We estimate an emission pathway countering a hypothetical eruption 3 times the size of Mount Pinatubo in 1991. We use a global climate model to evaluate global and regional responses to the eruption, with and without counteremissions. We then raise practical, financial, and ethical questions related to such a strategy. Unlike the more commonly discussed geoengineering to mitigate warming from long-lived greenhouse gases, designed emissions to counter temporary cooling would not have the disadvantage of needing to be sustained over long periods. Nevertheless, implementation would still face significant challenges.
Keywords: Antarktis; drivhusgasser; global klimamodell; global oppvarming; klimatologi; nedbør; polarområdene; vulkaner

Alien invasions in Antarctica - is anyone liable? - Hughes, Kevin A; Convey, Peter (Polar Research, 2014)
The introduction of non-native species to Antarctica in association with human activities is a major threat to indigenous biodiversity and the region's unique ecosystems, as has been well-demonstrated in other ecosystems globally. Existing legislation contained in the Protocol on Environmental Protection to the Antarctic Treaty does not specifically make the eradication of non-native species mandatory, although it is implicit that human-assisted introductions should not take place. Furthermore, to date, eradications of non-native species in the Treaty area have been infrequent and slow to progress. In 2005 an additional Annex (VI) to the Protocol was agreed concerning “Liability arising from environmental emergencies.” This annex focusses on prevention of environmental emergencies, contingency planning and reclaiming costs incurred when responding to an environmental emergency caused by another operator within the Antarctic Treaty area. However, the types of environmental emergencies covered by the annex are not defined. In this paper we highlight potential difficulties with the application of Annex VI in the context of non-native species control and eradication, including, for example, whether a non-native species introduction would be classified as an “environmental emergency” and therefore be considered under the terms of the annex. Even if this were the case, we conclude that the slow pace of approval of the annex by Antarctic Treaty Parties may prevent it coming into force for many years and, once in force, in its current form it is unlikely to be useful for reclaiming costs associated with the eradication or management of a non-native species.
Keywords: Antarktis; biodiversitet; internasjonal; miljøvern; politikk; samarbeid; økosystemer

At the root of the early penguin neck: a study of the only two cervicodorsal spines recovered from the Eocene of Antarctica - Jadwiszczak, Piotr (Polar Research, 2014)
The spinal column of early Antarctic penguins is poorly known, mainly due to the scarcity of articulated vertebrae in the fossil record. One of the most interesting segments of this part of the skeleton is the transitional series located at the root of the neck. Here, two such cervicodorsal series, comprising reinterpreted known material and a new specimen from the Eocene of Seymour Island (Antarctic Peninsula), were investigated and contrasted with those of modern penguins and some fossil bones. The new specimen is smaller than the counterpart elements in recent king penguins, whereas the second series belonged to a large-bodied penguin from the genus Palaeeudyptes. It had been assigned by earlier researchers to P. gunnari (a species of “giant” penguins) and a Bayesian analysis—a Bayes factor approach based on size of an associated tarsometatarsus—strongly supported such an assignment. Morphological and functional studies revealed that mobility within the aforementioned segment probably did not differ substantially between extant and studied fossil penguins. There were, however, intriguing morphological differences between the smaller fossil specimen and the comparative material related to the condition of the lateral excavation in the first cervicodorsal vertebra and the extremely small size of the intervertebral foramen located just prior to the first “true” thoracic vertebra. The former feature could have resulted from discrepancy in severity of external pneumatization. Both fossils provided valuable insights into the morphology and functioning of the axial skeleton in early penguins. Keywords: Antarctic Peninsula; La Meseta Formation; Palaeogene; early Sphenisciformes; cervicodorsal vertebrae.
Keywords: Antarktis; biologi; fossiler; morfologi; paleogen; pingviner

Reassembling Gondwana: A new high quality constraint from vibroseis exploration of the sub-ice shelf geology of the East Antarctic continental margin - Kristoffersen, Yngve; Hofstede, Coen; Diez, Anja; Blenkner, Richard; Lambrecht, Astrid; Mayer, Christoph; Eisen, Olaf (Journal of Geophysical Research: Solid Earth, 2014)
The breakup of Gondwana is manifested by coeval early Jurassic Karoo magmatism in South Africa and East Antarctica. In South Africa, the large volumes of volcanic rocks of the adjoining Lebombo and Mwenetzi-Save monoclines represent a volcanic rift margin, and in East Antarctica, a corresponding feature, the Explora Wedge is buried below sediments and floating ice shelves on the continental margin of Dronning Maud Land. We use the seismic vibrator source to explore the sub-ice geology in Antarctica, and the new seismic reflection and available regional aeromagnetic data enable us to outline a dogleg landward extent of the Explora Wedge in Dronning Maud Land. The congruent inboard wedge geometries on the two continents define a high quality constraint, which facilitate for the first time, a geologically consistent and tight reconstruction of Africa relative to East Antarctica within Gondwana. The uncertainties in correlations of major geological features (mobile belts) from one continent to the other may now be of the order of ten's of kilometers rather than hundreds of kilometers.
Keywords: Antarktis; geofysikk; geologi; kontinentalmargin; seismologi; stratigrafi

Complex network of channels beneath an Antarctic ice shelf - Langley, Kirsty; von Deschwanden, Angela; Kohler, Jack; Sinisalo, Anna; Matsuoka, Kenichi; Hattermann, Tore; Humbert, Angelika; Nøst, Ole Anders; Isaksson, Elisabeth (Geophysical Research Letters, 2014)
Ice shelves play an important role in stabilizing the interior grounded ice of the large ice sheets. The thinning of major ice shelves observed in recent years, possibly in connection to warmer ocean waters coming into contact with the ice-shelf base, has focused attention on the ice-ocean interface. Here we reveal a complex network of sub ice-shelf channels under the Fimbul Ice Shelf, Antarctica, mapped using ground-penetrating radar over a 100 km2 grid. The channels are 300–500 m wide and 50 m high, among the narrowest of any reported. Observing narrow channels beneath an ice shelf that is mainly surrounded by cold ocean waters, with temperatures close to the surface freezing point, shows that channelized basal melting is not restricted to rapidly melting ice shelves, indicating that spatial melt patterns around Antarctica are likely to vary on scales that are not yet incorporated in ice-ocean models.
Keywords: Antarktis; glasiologi; innlandsis; isshelf; satellite bilder; satellite mikrobølgesensorer

Assessing the importance of human activities for the establishment of the invasive Poa annua in Antarctica - Molina-Montenegro, Marco A; Carrasco-Urra, Fernando; Acuña-Rodriguez, Ian; Oses, Rómulo; Torres-Diaz, Cristian; Chwedorzewska, Katarzyna J (Polar Research, 2014)
Because of its harsh environmental conditions and remoteness, Antarctica is often considered to be at low risk of plant invasion. However, an increasing number of reports have shown the presence and spread of non-native plants in Antarctica; it is therefore important to study which factors control the invasion process in this ecosystem. Here, we assessed the role of different human activities on the presence and abundance of the invasive Poa annua. In addition, we performed a reciprocal transplant experiment in the field, and a manipulative experiment of germination with P. annua and the natives Colobanthus quitensis and Deschampsia antarctica, in order to unravel the effects of physical soil disturbance on the establishment and survival of P. annua. We found a positive correlation between abundance of P. annua and level of soil disturbance, and that survival of P. annua was 33% higher in sites with disturbed soil than non-disturbed. Finally, we found that disturbance conditions increased germination for P. annua, whereas for native species germination in experimentally disturbed soil was either unchanged or reduced compared to undisturbed soil. Our results indicate that human activities that modify abiotic soil characteristics could play an important role in the abundance of this invasive species. If the current patterns of human activities are maintained in Antarctica, the establishment success and spread of P. annua could increase, negatively affecting native flora. Keywords: Alien species; Colobanthus quitensis; Deschampsia antarctica; human disturbance; Poa annua; tourists.
Keywords: Antarktis; biodiversitet; flora; menneskelig påvirkning; planter; turisme; økosystemer

Selected elements in surface waters of Antarctica and their relations with the natural environment - Nędzarek, Arkadiusz; Tórz, Agnieszka; Drost, Arkadiusz (Polar Research, 2014)
The aim of the study was to specify the concentration of selected chemical elements in surface waters of King George Island, off the western coast of the Antarctic Peninsula. The research encompassed six streams, a lake and an artificial water reservoir located on the western coast of Admiralty Bay. Measured hydrochemical parameters included pH, conductivity, total dissolved solids (TDS), and total and dissolved forms elements such as Al, Co, Ni, Cu, Zn, Cd, Pb, Mn, Fe, As and Se. The values of pH, conductivity and TDS had the following ranges: 6.09–8.21, 6.0–875 µS cm−1 and 7.0–975 mg/L, respectively, and were typical for surface waters of Antarctica. Wide disparities were discovered regarding concentrations of the investigated elements, ranging from <0.01 µg/L for Cd to 510 µg/L for Fe, and differing from one water body to another. The investigated elements are discussed with reference to environmental conditions and anthropogenic factors. Concentrations of total and dissolved forms of elements are considered in connection with the composition of soil in their surroundings and with atmospheric deposition, mostly such as that took place locally. The increased levels of Pb and Zn concentrations in the immediate proximity of a research station suggested anthropogenic contamination. Keywords: Antarctic surface waters; total and dissolved elements; baseline elements values; anthropogenic metal contamination.
Keywords: Antarktis; biologi; geokjemi; hydrokjemi; kjemiske analyser; overflatevann

Deterrent activities in the crude lipophilic fractions of Antarctic benthic organisms: chemical defences against keystone predators - Núñez-Pons, Laura; Avila, Conxita (Polar Research, 2014)
Generalist predation constitutes a driving force for the evolution of chemical defences. In the Antarctic benthos, asteroids and omnivore amphipods are keystone opportunistic predators. Sessile organisms are therefore expected to develop defensive mechanisms mainly against such consumers. However, the different habits characterizing each predator may promote variable responses in prey. Feeding-deterrence experiments were performed with the circumpolar asteroid macropredator Odontaster validus to evaluate the presence of defences within the apolar lipophilic fraction of Antarctic invertebrates and macroalgae. A total of 51% of the extracts were repellent, yielding a proportion of 17 defended species out of the 31 assessed. These results are compared with a previous study in which the same fractions were offered to the abundant circum-Antarctic amphipod Cheirimedon femoratus. Overall, less deterrence was reported towards asteroids (51%) than against amphipods (80.8%), principally in sponge and algal extracts. Generalist amphipods, which establish casual host–prey sedentary associations with biosubstrata (preferentially sponges and macroalgae), may exert more localized predation pressure than sea stars on certain sessile prey, which would partly explain these results. The nutritional quality of prey may interact with feeding deterrents, whose production is presumed to be metabolically expensive. Although optimal defence theory posits that chemical defences are managed and distributed as to guarantee protection at the lowest cost, we found that only a few organisms localized feeding deterrents towards most exposed and/or valuable body regions. Lipophilic defensive metabolites are broadly produced in Antarctic communities to deter opportunistic predators, although several species combine different defensive traits. Keywords: Antarctic invertebrates; Antarctic algae; chemical ecology; sea star Odontaster validus; amphipod Cheirimedon femoratus; chemical defence.
Keywords: Antarktis; alger; kjemisk økologi; virvelløse dyr

Norway in the Antarctic - Rognhaug, Magnus Hovind (ed.) (Norsk Polarinstitutt, Norge Utenriksdepartementet, 2014)
Keywords: Antarktis; Antarktistraktaten; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene

Recent climate tendencies on an East Antarctic ice shelf inferred from a shallow firn core network - Schlosser, Elisabeth; Anschütz, Helgard; Divine, Dmitry; Martma, Tõnu; Sinisalo, Anna; Altnau, Sebastian; Isaksson, Elisabeth (Journal of Geophysical Research: Atmospheres, 2014)
Nearly three decades of stable isotope ratios and surface mass balance (SMB) data from eight shallow firn cores retrieved at Fimbul Ice Shelf, East Antarctica, in the Austral summers 2009–2011 have been investigated. An additional longer core drilled in 2000/2001 extends the series back to the early eighteenth century. Isotope ratios and SMB from the stacked record of all cores were also related to instrumental temperature data from Neumayer Station on Ekström Ice Shelf. Since the second half of the twentieth century, the SMB shows a statistically significant negative trend, whereas the δ18O of the cores shows a significant positive trend. No trend is found in air temperature at the nearest suitable weather station, Neumayer (available since 1981). This does not correspond to the statistically significant positive trend in Southern Annular Mode (SAM) index, which is usually associated with a cooling of East Antarctica. SAM index and SMB are negatively correlated, which might be explained by a decrease in meridional exchange of energy and moisture leading to lower precipitation amounts. Future monitoring of climate change on the sensitive Antarctic ice shelves is necessary to assess its consequences for sea level change.
Keywords: Antarktis; brehylle; geofysikk; geologi; glasiologi; havnivåstigning; isbrem; isshelf; klimaendringer; meteorologi; stabile isotoper

Age-Related Mercury Contamination and Relationship with Luteinizing Hormone in a Long-Lived Antarctic Bird - Tartu, Sabrina; Bustamante, Paco; Goutte, Aurélie; Cherel, Yves; Weimerskirch, Henri; Bustnes, Jan Ove; Chastel, Olivier (PloS One, 2014)
Seabirds, as long-lived top predators, accumulate contaminants such as mercury (Hg), an established endocrine disruptor. In long lived species hormonal secretion varies with age; therefore, Hg-induced endocrine disruption may be exacerbated in some age classes. Here we investigated relationships between blood total Hg and luteinizing hormone (LH, a key pituitary hormone for the onset of breeding), in pre-laying known-age (11–45 years old) snow petrels (Pagodroma nivea) from Adélie Land, Antarctica. We predicted that 1) blood Hg would increase with advancing age as a consequence of bio-accumulation; and that 2) increasing blood Hg would be related to decreased concentrations of LH in the most Hg-contaminated individuals. Hg concentrations were higher in females than in males (p<0.001), and contrary to our prediction, decreased with advancing age in males (p = 0.009) and tended to do so in females (p = 0.06). The analysis of stable isotopes (δ13C and δ15N) suggested that this unexpected pattern could originate from age and sex-related variations in trophic niche, and hence Hg exposure. Regarding LH, our prediction was only supported in young birds (≤23 years) where baseline LH was inversely correlated with Hg concentrations (p = 0.04). Hg burden did not predict baseline LH or GnRH-induced LH in birds that were more than 23 years old. These results show that age and contaminants may interfere with major endocrine mechanisms and, together with other recent studies, support the view that Hg could be connected to LH secretion and could then impair the fitness of long-lived birds.
Publisher: Public Library of Science
Keywords: Antarktis; forurensning; kjemiske analyser; miljø; nevrobiologi; ornitologi; petreller; sjøfugler; stabile isotoper; zoologi; økologiske nisjer